Rancang Bangun Prototype Alat Pengusir Tikus Dengan Pemanfaatan Gelombang Ultrasonik Berbasis Internet Of Things - Tijaniyah Tijaniyah; Sabda Alam Arzenda (Jurnal JEETech, 2022)
Rats are rodents that bring harm, both at home and industry. Rats running around the house (Rattus rattus, Rattus tanezumi and other types) are quite annoying for many people. However, with the current development of science and technology, especially in the field of electronics, there is one system that is offered to repel mice, namely ultrasonic sound technology, therefore this study aims to design a mouse mouse mouse using ultrasonic waves based on the internet of things. The method used in this study is the observation method in the form of an experiment from a prototype rat repellent to be designed, besides that this research will also use a literature study method by reading journals as a reference to get the best method used/combined in designing a prototype rat repellent device with the use of waves. ultrasonic internet of things (IoT) based. From the series of tests carried out, see the success rate of achieving the test criteria. So it can be concluded that this tool is sufficient to repel rat pests with ultrasonic sound. However, the application of rat expulsion using ultrasonic sound does not have an impact on rat pests directly, because based on the tests carried out, it takes some time for rats to be affected or disturbed by ultrasonic sound. The design of a prototype mouse repellent device using ultrasonic waves has been successfully carried out using a PIR sensor as a mouse movement detector, a sensor as an input that is read by a microcontroller which is then processed and sent to Blynk via internet connectivity. The results of the ultrasonic sound generator test show that it is able to make mice disturbed with a few seconds of delay. The relay response to respond to commands from Blynk is 1 second.